IMPLICATIONS OF IMPLEMENTING EDUCATION AND LEARNING IN HIGHER EDUCATION INSTITUTIONS POST COVID-19: OVERVIEW OF CHALLENGES AND STRATEGIC POLICIES - Iping, Baso (Universitas Ekasakti, 2022)
This study aims to find out how the challenges of higher education institutions are after the Covid-19 pandemic and what are the strategic policies of higher education institutions in the implementation of post-covid-19 education and learning. The method used is descriptive method and the data collection method is through field research and literature. The data were then analyzed descriptively qualitatively. The results obtained: First, the challenges of higher education institutions after the Covid 19 pandemic are: (a) Closing of educational institutions; (b) Creation of learning materials or content; (c) The level of achievement of learning targets is not optimal; (d) The online lecture system has not been fully followed by adequate lecturer capacity; and (e) The transformation of digital learning also has the effect of fatigue conditions and increased stress. Second, various strategies for educational institutions after the Covid-19 pandemic are: (a) Lecturers and students must improve internet and computer literacy skills; (b) Redefining learning outcomes: (c) Lecturers must ensure the readiness of lecture materials with perspective; (d) Determine the duration of each learning unit: (e) Assessment in the form of quizzes and independent assignments must be ready; and (f) Campuses must prepare sufficient infrastructure and bandwidth.